2014
DOI: 10.1038/jid.2013.279
|View full text |Cite
|
Sign up to set email alerts
|

CD164 and FCRL3 Are Highly Expressed on CD4+CD26 − T Cells in Sézary Syndrome Patients

Abstract: Sézary syndrome (SS) cells express cell surface molecules also found on normal activated CD4 T cells. In an effort to find a more specific surface marker for malignant SS cells, a microarray analysis of gene expression was performed. Results showed significantly increased levels of mRNA for CD164, a sialomucin found on human CD34+ hematopoietic stem cells, and FCRL3, a molecule present on a subset of human natural T regulatory cells. Both markers were increased in CD4 T cells from SS patients compared to healt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
29
0
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 37 publications
(36 citation statements)
references
References 33 publications
6
29
0
1
Order By: Relevance
“…The role of CD164 is ambiguous and remains unclear in the aforementioned studies; the results of the present study support the hypothesis that CD164 inhibits cell proliferation (17)(18)(19)(20)(21)(22)27,28).…”
Section: -Year Locoregional Controlsupporting
confidence: 85%
See 2 more Smart Citations
“…The role of CD164 is ambiguous and remains unclear in the aforementioned studies; the results of the present study support the hypothesis that CD164 inhibits cell proliferation (17)(18)(19)(20)(21)(22)27,28).…”
Section: -Year Locoregional Controlsupporting
confidence: 85%
“…Thus, they suggested that increased CD164 expression is involved in ovarian cancer progression through the stromal cell-derived factor 1a/C-X-C chemokine receptor type 4 axis, which promotes tumourigenicity. Wysocka et al (20) evaluated 6 patients with Sézary syndrome and 3 healthy donors, and identified that CD164 could be used to diagnose and monitor cases of the disease. This potential diagnostic role was also observed by Guenova et al (19) who investigated CD164 expression in malignant T-cells from 8 patients with…”
Section: -Year Locoregional Controlmentioning
confidence: 99%
See 1 more Smart Citation
“…© American Society for Clinical Pathology from patients with either advanced stage MF or the more aggressive variant of CTCL, Sézary syndrome (SS). 9,[17][18][19][20] Indeed, identification of CD4+ T cells lacking CD26 and/or CD7 by FC is a widely accepted strategy to quantify peripheral blood tumor cells in both MF and SS, with profound implications for staging and prognosis. 5,9,21 16 precluding the utilization of CD26 negativity as a sole marker to distinguish neoplastic from background reactive T cells in biopsy specimens.…”
Section: Discussionmentioning
confidence: 99%
“…As a multifunctional protein, CD164 acted as a surface marker of hematopoietic stem cells, a CXCR4 promoter activity‐enhancing transcription factor, and a stem cell‐specific marker inducer 9, 10, 11. High expression of CD164 was found in several malignant diseases and was associated with clinical outcomes of patients 13, 23, 28, 29, 30, 31. In lung cancer, the positive associations were significantly existed between CD164 expression and tumor size, tumor cell grading, and lymph node involvement 14.…”
Section: Discussionmentioning
confidence: 97%